2016
DOI: 10.4236/fns.2016.75040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Hematological and Biochemical Health Benefit Effects of <i>Hibiscus sabdariffa</i> Lin Dried Calyces Beverage in Human

Abstract: Background/Objective: This study was carried out to investigate the health benefit effects of Hibiscus sabdariffa Lin (H. sabdariffa L.) dried calyces beverage on some clinical, biochemical and hematological parameters in humans. Methods: The dried calyces were harvested in the two regions (Adamaoua and West) of Cameroon. The proximate, mineral composition and phytochemical screening were evaluated. A standardized extraction procedure was set up and from the calyces; we prepared a drink for 32 male volunteers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…These findings are in line with previous similar studies in 25 British male participants with 1-10% risk of cardiovascular disease ( 2 ), in 65 non-smoking pre- to mild hypertensive patients (70% Caucasians, aged 30-70 years) ( 3 ), in 60 Iranian diabetic patients with mild hypertension ( 5 ) and in 32 African male subjects (aged 21-32) ( 6 ). Interestingly, a H. sabdariffa isotonic drink was reported to be capable of increasing the physical fitness index of healthy respondents ( 25 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in line with previous similar studies in 25 British male participants with 1-10% risk of cardiovascular disease ( 2 ), in 65 non-smoking pre- to mild hypertensive patients (70% Caucasians, aged 30-70 years) ( 3 ), in 60 Iranian diabetic patients with mild hypertension ( 5 ) and in 32 African male subjects (aged 21-32) ( 6 ). Interestingly, a H. sabdariffa isotonic drink was reported to be capable of increasing the physical fitness index of healthy respondents ( 25 ).…”
Section: Resultssupporting
confidence: 89%
“…A study on 32 African male subjects (aged 21-32) in Cameroon, Central Africa, showed that consuming 500 ml H. sabdariffa drink twice a day for 2 weeks resulted in a significant increase in erythrocyte counts, hemoglobin levels, packed cell volume, mean platelet volume, high-density lipoprotein (HDL), triglycerides and creatinine levels, as well as significantly reducing leucocytes counts, MID cells, low-density lipoprotein (LDL) and total cholesterol levels. It was reported that there was no significant change in blood glucose, L-aspartate aminotransferase, L-alanine aminotransferase and urea levels ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, consumption of cold Hibiscus beverage induced a significant decrease (p < 0.05) in total W.B.Cs count compared with untreated lead-exposed group. This result was in harmony with Tazoho et al (2016). The W.B.Cs count is an important indicator for the strength of the immune system, as they protect body cells against pathogens.…”
Section: Hematological Indices In Liver and Serumand Cbc Parameterssupporting
confidence: 60%
“…The hematological effects of Roselle beverages in the present study were in line with Ejere et al (2013) who noticed significant (p < 0.05) increase in R.B.Cs, Hb and PCV values as a result of consuming aqueous extract of H. sabdariffa L. calyces by normal male albino rats. In male volunteers given Roselle beverage for 2 weeks, Tazoho et al (2016) observed significant (p < 0.05) elevation in the levels of R.B.Cs, Hb and PCV, which clearly indicates that the beverage contains phytochemical compounds, mainly anthocyanins, that stimulate the formation of erythropoietin, a glycoprotein which stimulates stem cells in bone marrow to produce red blood cells, in the stem cells (erythropoiesis) as well as the decreasing in the destruction of matured R.B.Cs (Kaur &Kapoor, 2005 andOhlsson &Aher, 2010).…”
Section: Hematological Indices In Liver and Serumand Cbc Parametersmentioning
confidence: 99%
“…These latest have reported potassium, calcium, magnesium, iron, zinc, sodium and copper contents of 2060, 1583, 316, 37.8, 6.5, 5.5 and 0.6 mg/100 g DW, respectively. Tazoho et al (2016) also reported the mineral contents of H. sabdariffa calyxes of 770.6, 77.8, 52.0, 1.10, 3.25 and 0.56 mg/100 g DW, respectively, for Ca, Mg, K, Na, Fe and Zn. The most likely reason for this difference in mineral contents was that the mineral composition of each plant organ is determined by a sequence of events.…”
Section: Mineral Contentmentioning
confidence: 85%